Immunization status and factors influencing hepatitis B vaccination of preterm infants in three provinces of China, 2019 to 2021 - Huang, Li-fang; Huang, Ao-di; Zhang, Xue; Tang, Lin; An, Jing; Li, Jun; Zheng, Hui; Yin, Zun-dong; Wang, Fu-zhen (BMC infectious diseases, 2024)
Premature infants have less physiologic reserve and often delayed vaccination compared to full-term infants. The birth dose of hepatitis B vaccine (HepB-BD) is an essential measure to achieve the goal of "zero infections" of hepatitis B virus in all newborns. However, there are few investigations of hepatitis B vaccination of preterm infants, leading to uncertainty of coverage and insufficient knowledge of factors influencing timely vaccination of this important population. We obtained hepatitis B vaccine (HepB) vaccination histories of premature infants born during 2019-2021 in three provinces from the respective provincial immunization information systems. Extracted data included date of birth, sex, region, and dates of HepB administration. We conducted descriptive analyses that included basic characteristics of the study subjects, HepB-BD administration, and full-series HepB vaccination. Factors potentially influencing HepB-BD and full series vaccination were analyzed by logistic regression. There were 1623 premature infants included in the analytic data set. Overall HepB-BD coverage was 71.41%; coverage among premature infants born to mothers with unknown hepatitis B surface antigen (HBsAg) status was 69.57%; coverage was higher at county-level-and-above hospitals (72.02%) than hospitals below county level (61.11%). Full-series HepB coverage was 94.15%; full-series coverage among preterm infants weighing less than 2000 g at birth was 76.92%. Logistic regression showed that the HepB-BD vaccination rate was positively associated with being born to an HBsAg-positive mother and being preterm with high birth weight. Regression analysis for factors influencing full-series HepB coverage showed that being born prematurely was positively associated with full-series coverage and being premature with a very low birth weight was negatively associated with full-series coverage. HepB-BD coverage levels in three provinces of China were less than the target of 90%, especially among premature infants born to mothers with unknown HBsAg status and at hospitals below the county level. Screening of pregnant women should be a universal normal standard. Hepatitis B vaccination training should be strengthened in hospitals to improve the HepB-BD vaccination rate of premature infants and to effectively prevent mother-to-child transmission of hepatitis B virus.